Perceptions and Factors Associated with Self-Medication for Oral Health Problems in Dental Patients of LUMHS, Jamshoro: Self-Medication for Oral Health Problems in Dental Patients - Shah, Farwa; Rajpar, Shazia Parveen; Talpur, Nida; Kandhro, Rehmatullah; Shah, Sana; Shah, Maham; Chandio, Benish (Pakistan Journal of Health Sciences, 2025)
The practice of self-medication is widespread in both industrialized and developing nations. It is characterized by the use of medications to treat self-diagnosed conditions and the prescription of medications without appropriate professional advice. However, the illogical use of antibiotics contributes to antibiotic resistance nd has several negative repercussions. Objectives: To assess the perceptions and factors associated with self-medication for oral health problems among dental patients of Liaquat University of Medical and Health Sciences, Jamshoro. Methods: 335 respondents were included in this cross-sectional study conducted at the Oral Diagnosis Departments of Liaquat University of Medical and Health Sciences, Jamshoro. The study was completed in a time duration of two months by employing a non-probability consecutive sampling technique. The data were subjected to descriptive analysis. SPSS Version 26.0 was employed to analyze the data. Results: 73% of total subjects were taking self-medication as the reason for minor illness (36.3%). Most of the patients were affected by having age of 18-30 years (45.4%) and female had more predilection (54.9%). Toothache was the most common cause of self-treatment (49.4%), pain relievers were the most common drugs taken as self-medication (24.5%), and Friends and relatives were the main sources of advice (59.2%). Conclusions: It was concluded that self-medication for dental illnesses was quite popular among patients. Although the majority of patients got symptomatic relief through self-medication all the respondents agreed that this was not the right practice and that proper consultation is important. Literacy level had a bad impact on people’s choices of self-treatment.